Analisis Fungsi Kelompok Tani dalam Pengembangan Usahatani Jagung di Desa Langku-Langku Kecamatan Tiworo Tengah Kabupaten Muna Barat - Wa Ode siti Anisa; Sukmawati Abdullah; Mardin Mardin (Fakultas Pertanian Universitas Halu Oleo, 2022)
The role of farmer organizations in corn growing development in Langku-langku Village, Tiworo Tengah District, West Muna Regency. This study took place between June and 2021. The census method was employed for sampling, and data deskriptif methods and income formulae were used for data analysis.. The results of the study: 1) Farmers' groups function as learning classes for farmers by providing information for farmers regarding corn market information to improve skills in managing corn crops. As a vehicle for cooperation, farmer groups strengthen cooperation among farmers by working together when processing, marketing their products and expenses and building cooperation with corn suppliers in West Muna. As a production unit, the farmer group provides a jonder machine and a machine that separates corn seeds and cobs.